Characterization of hepatitis E virus natural infection in farmed rabbits. Issue 1 (14th September 2020) - Li, Shuangshuang; Li, Manyu; He, Qiyu; Liang, Zhaochao; Shu, Jingyi; Wang, Lin; Wang, Ling
Abstract: Rabbit hepatitis E virus (HEV3‐ra) is widely distributed in rabbits worldwide and several recent reports found that HEV3‐ra can infect humans. Therefore, people exposed to rabbits are at high risk of HEV infection. This study was conducted to investigate the characteristics and outcomes of HEV3‐ra natural infection in rabbits. Seventy farmed rabbits (3‐month‐old) were surveyed in a farm in Beijing, China. Rabbits tested positive for HEV RNA were followed weekly for testing of HEV RNA, antigen, antibody and alanine aminotransferase (ALT) level. Liver and kidney tissue was collected for histopathology. Complete genome sequencing of the isolated HEV3‐ra strain was performed (CHN‐BJ‐r4, GenBank: MT364355). The infectivity of CHN‐BJ‐r4 was tested in ten naïve rabbits by intravenous injection or gavage. Anti‐HEV antibody and HEV RNA were tested positive in 7.14% (5/70) and 11.4% (8/70) of rabbits, respectively. Eight naturally infected rabbits were followed, and 37.5% (3/8) of the observed rabbits were found to have fecal shedding of HEV ranging from 3‐22 weeks with high viral load (10 5 ‐10 7 copies/g). Two out of eight rabbits showed temporary viremia. Naturally infected rabbits presented elevated ALT level, seroconversion, and liver histopathology. Complete genome of HEV3‐ra isolated in this study shared 84.61%‐94.36% nucleotide identity with known HEV3‐ra complete genomes. The isolated HEV3‐ra strain was infectious and could infect other rabbits through intravenous and fecal–oral route. Naturally infected rabbits showed up to 22‐week fecal virus shedding with high viral load. These features increased the risk of rabbit‐to‐rabbit and rabbit‐to‐human transmission.